Management systems by performance indicators of higher education institutions: proposal of a model - Lugoboni, Leonardo Fabris; Correa, Hamilton Luiz; Araujo, Juliano Augusto Orsi; Chiareto, Joice (Revista de Administração da UFSM, 2021)
Purpose – This research aims to recognize the performance indicators relating to the management of species reported in the literature. Design/methodology/approach – It is an exploratory and descriptive research. It assumes the qualitative characteristics. We presented a theoretical proposal of indicators and sufficient dimensions to manage an IES. The board was selected by convenience. The expert group was composed of people who have expertise in managing performance. Findings – We found indicators that were added according to the suggestion of the respondents, resulting in 65 indicators, divided into 9 dimensions. The model contemplates the dimensions: Economic; Internationalization and research; Student/Client; Market; Academia; Operational; Human Resources; Society/extension and Sustainability. Research limitations/implications – As limitations of the research, there is the possibility of some work on indicators that have not been identified at this stage of research, and also the choice of specialists. Practical implications – This study presents the determinants of business performance. The indicators that should be used for each type of organization are of utmost importance and were highlighted as one of the challenges of future research in the management of organizational performance. Social implications – In the Brazilian literature, 75% of the surveys do not address performance management holistically, thus reinforcing this study's importance and originality. Originality/value – Previous literature were identified 57 performance indicators, distributed in six 6 dimensions based on the concepts of multidimensionality. The work found indicators were added according to the suggestion of the interviewees, resulting in 65 indicators divided into 9 dimensions.